Hirschsprung Disease: The Rise of Structured Transition and Long-term Care. Issue 3 (September 2019) - Harrington, Amanda W.; Gasior, Alessandra C.; Einarsdottir, Hulda; Rothstein, David H.; Rollins, Michael D.; Ozgediz, Doruk E.
Abstract : ABSTRACT: Hirschsprung disease, like most surgically correctable congenital anomalies, is now survivable well into adulthood. Patients are, therefore, presenting later in life with problems that were previously infrequently encountered by colorectal surgeons or gastroenterologists. The goals of our review are to describe the current state of care transition for this patient population, identify the specific needs for these patients, and propose guidelines which could inform a future model of transition from the pediatric to adult setting. This is a review of the current state of care transition and long-term outcomes for patients with Hirschsprung disease. Although these patients report a generally good quality of life, the majority suffer from some degree of lifelong gastrointestinal complication, regardless of the type of operative repair. A more formalized transition of care will provide a guide for pediatric surgeons and patients, alleviate colorectal surgeon and gastroenterologist concerns, and provide better long-term care for these patients. Abstract : Supplemental Digital Content is available in the text